The importance of pathogenicity factors of some Streptococcus spp. and Klebsiella spp. in determining their etiological role in the inflammatory processes of the respiratory tract - L. A. Kraeva; E. S. Kunilova; O. A. Burgasova; G. N. Hamdulaeva; E. M. Danilova; G. I. Bespalova (Инфекция и иммунитет, 2020)
Together with the known pathogens of inflammatory processes of the respiratory tract in clinical practice are often found representatives of Streptococcus and Klebsiella, previously considered commensals of the mucous membranes of the upper respiratory tract. The exchange of genetic information facilitates the transfer of virulence factors between strains not only within the species but also within the genus. In such cases, the acquisition of virulence genes by nonpathogenic species from representatives of pathogenic species contributes to the manifestation of previously not typical properties. Therefore, the aim of the research was to study the virulence of opportunistic Streptococcus spp. and Klebsiella spp. in inflammatory processes of the respiratory tract and substantiate their etiological role in the development of the disease. We studied 220 strains of Streptococcus spp. and 97 strains of Klebsiella spp., isolated from patients with inflammatory processes in the respiratory tract and from healthy individuals. Strains of Streptococcus spp. were investigated for the presence of virulence genes: sagA, lmb, fapl, ply, lytA. Strains of Klebsiella spp. were examined for the presence of virulence genes: MrkD, magA, kfu. The phenotypic marker of lmb gene expression in Streptococcus and MrkD gene in Klebsiella was the indicator of adhesion of isolated strains to buccal epithelial cells. Expression of the fapl gene was evaluated in a phenotypic biofilm formation test. In individuals with upper respiratory tract inflammation, the most common types of strepto -cocci were: S. mitis, S. anginosus, and S. oralis. Strains of these species isolated from inflammatory processes in the upper respiratory tract had 2—4 times greater adhesiveness than strains isolated from healthy individuals. Phenotypic determination of the ability to biofilm formation showed that strains of Streptococcus containing the fapl gene formed a dense biofilm in contrast to strains without the fapl gene. K. oxytoca strains isolated from people with sinusitis had mrkd, magA, and kfu virulence genes that are characteristic of K. pneumoniae strains. In phenotypic tests, it was found that the value of the adhesion index in K. oxytoca strains isolated from patients is 4 times higher than in strains of this species isolated from healthy individuals. Thus, to confirm the etiological role of an opportunistic microorganism in the development of the infectious process, it is necessary to be guided by data on the genetic and phenotypic markers of virulence of the isolated strain.